INFRARED DRYING CHARACTERISTICS OF BEAN SEEDS - Doymaz, Ibrahim (WILEY, 2015)
The effect of different infrared power levels on drying kinetics of red kidney bean seeds was investigated. The bean seeds were dried at 83, 125, 167 and 209 W infrared power levels and constant seed diameter is 1.14 cm. It is observed that drying characteristics of bean seeds were greatly influenced by infrared power. The drying data were fitted with 10 thin-layer drying models available in the literature. According to the results, Midilli et al. model is superior to the other models for explaining the drying kinetics of bean seeds. Effective moisture diffusivity was calculated and was between 1.75 x 10(-9) and 1.02 x 10(-8) m(2)/s within the studied infrared power level range. Activation energy was estimated by a modified Arrhenius-type equation and found to be 9.54 kW/kg.
Keywords: MOISTURE DIFFUSIVITY; ENERGY-CONSUMPTION; KINETICS; QUALITY; TOMATO; FRESH; MODEL; COLOR; Food Science & Technology